Pemenuhan Hak Mediasi Dalam Perkara Perceraian Untuk Narapidana Dibawah Lima Tahun - azka, ifada; Maulana, M Irfan; Ayu Ningtias, Shavira (Muhammadiyah University of Surabaya, 2025)
It is important to discuss the fulfillment of the right to mediation in divorce cases for inmates under five years old so that we can find out about the rights of inmates who have not been fulfilled in divorce cases. The purpose of this writing is so that inmates continue to follow the steps in the case and the inmates continue to get their rights. The focus of this research is on the relationship between prisoners' rights and mediation as well as the relationship between prisoners' mediation rights in divorce cases. This research includes normative research, by taking data sources in the form of books, journals, and articles. The results of the study show that descriptive analysis is used. (1) There is a legal void in the fulfillment of the rights of prisoners under five years to be able to participate in mediation in divorce cases. (2) There is a legal void in the right of prisoners under five years to be able to participate in mediation in divorce cases.